Triage protocol for allocation of critical health resources during Covid-19 pandemic and public health emergencies. A narrative review: Triage protocol during the COVID-19 health emergency. - Iacorossi, Laura; Fauci, Alice J.; Napoletano, Antonello; D'Angelo, Daniela; Salomone, Katia; Latina, Roberto; Coclite, Daniela; Iannone, Primiano (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work. Triage during the Covid-19 pandemic can impose difficult allocation decisions when demand for mechanical ventilation or intensive care beds greatly exceeds available resources. Triage criteria should be objective, ethical, transparent, applied equitably and publically disclosed. The aim of this review is to describe the triage tools and process for critical care resources in a pandemic health emergency. Methods. A narrative review was conducted of the literature on five electronic databases, namely PubMed, CINHAL, Web of Science, Cochrane and Embase, searching for studies published from 2006 to June 2020. Results. The results describe different triage tools. A gold standard of triage does not exist for the adult or paediatric population. Using probability of short-term survival as the sole allocation principle is problematic. In general, each triage protocol should be applied with a specific ethical justification, including transparency, duty to care, duty to steward resources, duty to plan, and distributive justice. Conclusions. Clinical triage decisions based on clinical judgment alone are prone to inconsistent application by triage officers in a pandemic. An ethical framework can inform decision-making and improve accountability. It remains difficult to connect clinical criteria and ethical criteria, because of the models on offer for health services.